Abnormal cerebellar volume in acute and remitted major depression - Depping, Malte S.; Wolf, Nadine D.; Vasic, Nenad; Sambataro, Fabio; Hirjak, Dusan; Thomann, Philipp; Wolf, Robert Christian (Progress in neuro-psychopharmacology & biological psychiatry, 2016)
Abnormal cortical volume is well-documented in patients with major depressive disorder (MDD), but cerebellar findings have been heterogeneous. It is unclear whether abnormal cerebellar structure relates to disease state or medication. In this study, using structural MRI, we investigated cerebellar volume in clinically acute (with and without psychotropic treatment) and remitted MDD patients. High-resolution structural MRI data at 3T were obtained from acute medicated (n=29), acute unmedicated (n=14) and remitted patients (n=16). Data from 29 healthy controls were used for comparison purposes. Cerebellar volume was investigated using cerebellum-optimized voxel-based analysis methods. Patients with an acute MDD episode showed increased volume of left cerebellar area IX, and this was true for both medicated and unmedicated individuals (p<0.05 cluster-corrected). Remitted patients exhibited bilaterally increased area IX volume. In remitted, but not in acutely ill patients, area IX volume was significantly associated with measures of depression severity, as assessed by the Hamilton Depression Rating Scale (HAMD). In addition, area IX volume in remitted patients was significantly related to the duration of antidepressant treatment. In acutely ill patients, no significant relationships were established using clinical variables, such as HAMD, illness or treatment duration and number of depressive episodes. The data suggest that cerebellar area IX, a non-motor region that belongs to a large-scale brain functional network with known relevance to core depressive symptom expression, exhibits abnormal volume in patients independent of clinical severity or medication. Thus, the data imply a possible trait marker of the disorder. However, given bilaterality and an association with clinical scores at least in remitted patients, the current findings raise the possibility that cerebellar volume may be reflective of successful treatment as well.
Gesehen am 07.05.2020